ANALISIS PENGGUNAAN WHATSAPP TERHADAP MOTIVASI BELAJAR PADA TIK SISWA SEKOLAH MENENGAH ATAS - Nisa, Wilya Choirun; Basrowi, Basrowi; Rahmadani, Kurniati (LPPM Universitas Bina Bangsa, 2023)
This study aims to analyze the use of Whatsapp on learning motivation in ICT subjects of grade XI students at SMAN 5 Serang City.The type of research used is qualitative research. This interview was conducted by 5 grade XI students, where the analysis was carried out in three steps, namely data reduction, data presentation, and conclusion pulling.The result of this study is that students use Whatsapp to discuss and communicate, as well as exchange information on material discussed at school. And the use of Whatsapp can affect their focus at school, but it depends on how the person uses it, and students during subjects also students do not play mobile phones because the mobile phones are taro or stored by the teacher. The conclusion of this study is that by providing motivation before holding tests in the class group, students will be more enthusiastic in doing assignments or related to learning. And teachers must also give rules for using mobile phones while studying and when in their spare time. This is so that students focus on following the lesson and the lesson can also enter their brain